Customs Of Wages in the Implementation of Marriages for the Community of Tanjungbalai City According to the Perspective of Islamic Law - Khairunnisa Siregar; Khairul Fahmi Simangunsong (AT-TAFAHUM: Journal of Law, 2018)
The purpose of this research is to know how wages are in marriage tradition on society of Tanjungbalai citizens, the value, and the answers of ulama on wage-upah tradition. This research uses the qualitative method. This research is in Tanjungbalai. The data collecting technique uses documentation, interviews and observation. Data analysis technique uses theme and formulate working hypothesis and analyze based on working hypothesis. Data source uses primary source and secondary source. The results of research show that the action of wages in marriage tradition on citizens of Tanjungbalai was carried out through several steps, they are; peace be upon on tahmid, tasykir and takhtim speech (first), peace be upon using shalawat on Muhammad SAW (second) the value in wage-upah is suggestion to couple marriage to keep strong unity in the family, keep namely of family beyond on the couple marriage, keep namely of neighbors, brothers and the group community around, wage-upah has closed of worship to the God (Allah SWT), and has normative values and local wisdom value. According to Ulama of Fikih about wage-upah has been divided into two ideas, according to Hanafi Fikih, many laws based on traditional culture, because many expressions common by al-Ma'ruf 'urfan ka al-Masyruth Syarthán, wa al-Tsabit bil 'urf ka al-Tsabit bi al-Nash (well done based on tradition similar to the value with conditions must be filled and well done on tradition with the value on nash. This is called by qawlun qodím.Besides of Hanafi fiqh, (Shafi'iyah, Hanbali and Maliki schools) all Ulama decided together that 'urf ṣaḥīḥ (in Qawlun Jadid) can be formed by hujjah along it's never be contradicted with syara' Ulama Malikiyah was familiar because of their statement that Ulama Madinah can be formed into Hujjah, and this is based on culture (norm tradition), as is culture done by citizen of Tanjungbalai in marriage using wages.